Can corporate philanthropy be driven from the bottom to the top? Evidence from China. Issue 5 (30th July 2019) - Zhang, Lin; Mo, Shenjiang; Chen, Honghui; Wu, Jintao
Abstract : Purpose: This paper aims to demonstrate that corporate philanthropy can be driven from the bottom to the top. In particular, the authors investigate whether employees' donations influence corporate philanthropy and under what conditions this effect occurs. Design/methodology/approach: The sample consists of Chinese listed firms that disclosed the amount employees donated in response to the Sichuan earthquake in 2008. The Heckman two-stage selection model is applied to examine the effect of employees' donations on corporate philanthropy and the conditions under which this effect occurs. Findings: The results show that employees' donations are positively associated with corporate philanthropy. Furthermore, a higher percentage of females in top management teams can significantly strengthen the effect of employees' donations on corporate philanthropy. When the average age of the top management team members is high, the influence of employees' donations on corporate philanthropy is stronger. Practical implications: This is an empirical study that helps to predict corporate philanthropy. Another practical implication is that employees should be recognized as an important element of corporate social responsibility. Social implications: The results encourage employees to become drivers of corporate social responsibility. Originality/value: This study contributes to the corporate social responsibility literature by demonstrating that corporate philanthropy can be driven from the bottom to the top. Moreover, this study integrates signaling theory into the study of corporate social responsibility. Finally, this study identifies two important contingent factors that strengthen the effect of employees on top managers' decisions about corporate social responsibility.